THE ROLE OF MOBILE APPS IN TEACHING ENGLISH FOR TECHNICAL STUDENTS: THE ROLE OF MOBILE APPS IN TEACHING ENGLISH FOR TECHNICAL STUDENTS - Kalmuratova, Ayzada (Журнал иностранных языков и лингвистики, 2025)
In today’s increasingly globalized and technology-driven world, English proficiency has become a fundamental requirement for technical students. As engineering, computer science, and other technical fields continue to evolve internationally, the ability to communicate effectively in English is no longer optional but essential. Mobile applications have emerged as powerful tools in this educational landscape, offering innovative ways to teach and learn English specifically tailored to the needs of technical students.